1, 2, 3-Triazole-fused spirochromenes as potential anti-tubercular agents: synthesis and biological evaluation. Issue 30 (9th May 2018) - Ashok, Dongamanti; Chiranjeevi, Pamula; Kumar, Aamate Vikas; Sarasija, Madderla; Krishna, Vagolu Siva; Sriram, Dharmarajan; Balasubramanian, Sridhar
Abstract : A convenient synthesis of novel prototypes containing the two pharmacophores of chromene and 1, 2, 3-triazole in a single molecular backbone, were evaluated against Mycobacterium tuberculosis H37Rv strain. Abstract : A facile and convenient approach has been designed for the synthesis of novel prototypes that possess the advantage of the two pharmacophores of chromene and 1, 2, 3-triazole in a single molecular backbone, were evaluated against Mycobacterium tuberculosis H37Rv strain. The new analogues 1, 2, 3-triazole-fused spirochromenes were accomplished in four step synthetic strategy utilizing click chemistry ([3 + 2] Huisgen cycloaddition) in the ultimate step. The synthesized compounds were established based on the spectral data and X-ray crystal structure for7a . Among the compounds tested against Mycobacterium tuberculosis H37Rv strain, some products exhibited potent antimycobacterial activity with minimum inhibitory concentration (MIC) values ranging from 1.56 to 6.25 μg mL −1 . Compounds exhibiting good in vitro potency in the MTB MIC assay were further examined for cytotoxicity in a RAW 264.7 cells. Compounds7a, 7d, 7i (MIC: 1.56 μg mL −1 ) and7k, 7m (MIC: 3.125 μg mL −1 ) exhibited promising hits.